Development and Validation of UV Spectrophotometric and RP-HPLC Methods for the Quantitative Estimation of Sitagliptin in Bulk Drug and Pharmaceutical Dosage Forms - D. Chaitanya Dixit; B. Swetha; Dr. J. Gopala Krishna; Dr. B.V. Ramana (The Bioscan, 2026)
Two simple, sensitive, precise, and economical analytical methods were developed and validated for the quantitative estimation of Sitagliptin in bulk drug and pharmaceutical dosage forms.